Environmental asbestos exposure sources in Korea. (1st October 2016) - Kang, Dong-Mug; Kim, Jong-Eun; Kim, Ju-Young; Lee, Hyun-Hee; Hwang, Young-Sik; Kim, Young-Ki; Lee, Yong-Jin
Abstract : Background: Because of the long asbestos-related disease latencies (10–50 years), detection, diagnosis, and epidemiologic studies require asbestos exposure history. However, environmental asbestos exposure source (EAES) data are lacking. Objectives: To survey the available data for past EAES and supplement these data with interviews. Methods: We constructed an EAES database using a literature review and interviews of experts, former traders, and workers. Exposure sources by time period and type were visualized using a geographic information system (ArcGIS), web-based mapping (Google Maps), and OpenWeatherMap. The data were mounted in the GIS to show the exposure source location and trend. Results: The majority of asbestos mines, factories, and consumption was located in Chungnam; Gyeonggi, Busan, and Gyeongnam; and Gyeonggi, Daejeon, and Busan, respectively. Shipbuilding and repair companies were mostly located in Busan and Gyeongnam. Conclusions: These tools might help evaluate past exposure from EAES and estimate the future asbestos burden in Korea.